Social Support Experiences of Spousally Bereaved Individuals in a South African Township Community: The Botho/Ubuntu Perspective - Thomas, Tsholofelo Angela (Frontiers in Psychology, 2021)
Bereavement is a deeply personal experience that is also shaped by one’s socio-cultural context. This qualitative study explored the social support experiences and needs of spousally bereaved individuals in a South African township. The botho/ubuntu philosophical framework was used to interpret participants’ experiences in this regard. Six ethnically diverse, bereaved spouses aged 55–67 years, residing in a predominantly Setswana-speaking township in the North-West Province of South Africa, were interviewed. Thematic analysis was used to analyze the data. An indigenous knowledge consultant was interviewed to situate participant experiences pertaining to mourning rites and traditions within the indigenous socio-historical and contemporary cultural context. The following themes were identified: i) Sources of social support during bereavement; ii) Inadequate social support after spousal death; iii) The need for grief counselling; and iv) Social restrictions and systematic isolation during the traditional mourning period: “It is as if you smell.” Broadly, bereaved spouses drew on their support networks at various stages of their bereavement, which included family members, in-laws, friends, burial societies, their surrounding communities, and religious communities and figures. However, some experienced ostracization and stigmatization during the mourning period, which was invariably longer for the widows in this study, in line with conventions across Black South African cultures. Some participants reported withdrawal of support by their in-laws and harmful attitudes and assumptions rooted in patriarchal ideology by family members and in-laws. As pertaining to botho/ubuntu, the study also showed that communality or relationality entailed both positive and negative aspects, including support, co-operation, care, lack of support, stigmatization, and ostracization. Unlike conventional conceptualizations of botho/ubuntu, the study findings illustrate the human experience as comprising varying dimensions of relationality, ranging from harmony to disharmony. Findings regarding the negative aspects of communality are compatible with those relating to relational interdependence in African and East Asian settings. The findings also expand our understanding of the nature of disharmony alongside harmony in interdependent socio-cultural contexts.